The Distribution of Eye-Colour in the Polish Population - Gronkiewicz, Lidia; Gronkiewicz, Stanisław (Anthropological Review, 1995)
Among adult males and females shows no regional differences in eye-colour, thus, the Polish population is homogenous as regards this trait. It is suggested that the regional differences in eye-colour, observed in Poland before World War II, declined in result of the post-war, massive migrations and resettlements of the Polish population.